Antimicrobial resistance of combat-related infections. Literature review - Burakov, O. V. (General Surgery, 2025)
The article compiles information from scientific reports published between 2011 and 2024 , indexed in both Ukrainian and international databases. The studies focus on the microflora of combat wounds and the antimicrobial resistance of primary pathogens responsible for purulent‑septic complications in patients from conflict zones. We analyzed the etiological structure of common wound infections and their antibiotic resistance in military personnel with combat‑related soft tissue injuries who were evacuated from the combat zone in eastern Ukraine.